Insulin Resistance Remission Following Laparoscopic Roux-en-Y Gastric Bypass and Laparoscopic Sleeve Gastrectomy in Chinese Type 2 Diabetes Mellitus Patients With a Body Mass Index of 27.5–32.5 kg/m2 - Luo, Ping; Cao, Yaoquan; Li, Pengzhou; Wang, Guohui; Song, Zhi; Li, Weizheng; Su, Zhihong; Zhou, Hui; Yi, Xianhao; Fu, Zhibing; Sun, Xulong; Tang, Haibo; et al. (Frontiers in Physiology, 2021)
Abstract Background Insulin resistance (IR) is closely associated with the pathogenesis of type 2 diabetes mellitus (T2DM). However, remission of insulin sensitivity after bariatric surgery in patients with T2DM and a body mass index (BMI) of 27.5–32.5 kg/m² has not been fully elucidated. Methods Thirty-six T2DM patients with a BMI of 27.5–32.5 kg/m² were prospectively consecutively recruited for laparoscopic Roux-en-Y gastric bypass (LRYGB) or laparoscopic sleeve gastrectomy. Hyperinsulinemic euglycemic clamp, oral glucose tolerance test (OGTT), and other indicators were tested at baseline and 6 months postoperative. Glucose disposal rate (GDR), time to reach euglycemia, homeostatic model assessment of IR, quantitative insulin sensitivity check index (QUICKI), triglyceride glucose index (TyG), 30-min insulinogenic index (IGI30), and disposition index (DI) were calculated at baseline and 6 months after surgery. The criterion for remission in T2DM patients was the achievement of the triple composite endpoint. Results Anthropometric and glucolipid metabolism parameters significantly improved following surgery. The GDR increased significantly from baseline to 6 months after LRYGB (from 4.28±1.70 mg/kg/min to 8.47±1.89 mg/kg/min, P<0.0001) and LSG (from 3.18±1.36 mg/kg/min to 7.09±1.69 mg/kg/min, P<0.001). The TyG index decreased after surgery (RYGB group, from 9.93±1.03 to 8.60±0.43, P<0.0001; LSG group, from 10.04±0.79 to 8.72±0.65, P=0.0002). There was a significant reduction in the IGI30 (RYGB group, from 2.04±2.12 to 0.83±0.47, P=0.005; LSG group, from 2.12±1.73 to 0.92±0.66, P=0.001). The mean DI significantly increased from 1.14±1.35 to 7.11±4.93 in the RYGB group (P=0.0001) and from 1.25±1.78 to 5.60±4.58 in the LSG group (P=0.003). Compared with baseline, HOMR-IR, QUICKI, area under the curve-C-peptide release test (AUC-CRT), and AUC-OGTT were significantly changed at 6 months postoperative. Overall, 52.63% of patients in the LRYGB group versus 29.41% of patients in the LSG group achieved the triple composite endpoint. Conclusion LRYGB and LSG effectively induced remission of IR in patients with T2DM and a BMI of 27.5–32.5 kg/m².